The Vocal Teaching in Early Childhood For Early Childhood Teachers of Nantong Normal College - Xia Qizhe; Meeson , Pranote; Kaosawang, Ampaipan (Journal of Roi Kaensarn Academi, 2024)
From the study of problems in teaching vocal in early childhood education. The researcher therefore wanted to study the methods and contents of vocal teaching for early childhood teachers in the School of Music and Dance, Nantong Normal College. It was found that vocal teaching is a vital aspect of early childhood education, focusing on developing sound vocal technique, providing advice on repertoire selection and performance, and fostering musical cognitive skills. Teachers use paralinguistic techniques to communicate attitudes and emotions, and research shows that children’s compositions represent awareness and are linked to musical cognitive skills. Vocal parenting nurtures singing, fostering musical cognitive skills and creativity. Acceptance and Commitment Therapy (ACT) for confidence in singing, rhythmic activities, and rotating lessons improve intonation skills. Vocal teaching also develops literacy skills through singing and playing, requiring proper vocal control and breath training.